Eating behaviors, body image, perfectionism, and self-esteem in a sample of Portuguese girls - Teixeira,Maria D. (2016)
Objective: Eating disorders are an increasingly prevalent health problem among adolescent girls. It is well known that biological, psychosocial, and family-related factors interact in the development of this group of disorders. However, the mechanisms underlying the interaction between these variables are still poorly understood, especially in Portuguese adolescents. The aim of this study was to investigate the relationship between eating behaviors, body dissatisfaction, self-esteem, and perfectionism in a sample of Portuguese girls. Method: A community sample of 575 Portuguese girls attending secondary school, answered self-report questionnaires including data on weight, height, and the Portuguese versions of the Contour Figures Rating Scale, the Child and Adolescent Perfectionism Scale, the Children Eating Attitudes Test, and the Rosenberg Self-Esteem Scale. SPSS version 20.0 for Windows was used for statistical analyses. Results: High scores in the Children Eating Attitudes Test were associated with significantly higher levels of body dissatisfaction (r = 0.339), socially prescribed perfectionism (r = 0.175), self-oriented perfectionism (r = 0.211), and low self-esteem (r = -0.292) (all p < 0.001). Self-oriented perfectionism partially mediated the relation between body dissatisfaction and disordered eating behaviors. Conclusion: In this sample, dysfunctional eating behaviors appeared to correlate strongly with body dissatisfaction, low self-esteem, and perfectionism in girls. These themes should be addressed among female adolescents in the community.